Canadian Arctic Search and Rescue: An Assessment - Goegebeur, Brynn (Université d'Ottawa | University of Ottawa, 2014)
This paper is a policy assessment of Canada’s search and rescue system with the purpose of examining to what extent Canada’s search and rescue resources are able to meet growing Arctic search and rescue demands. This assessment consists of three main sections. The first examining search and rescue in general; its structure, operation, rescue needs, as well as the country’s search and rescue capacity and capabilities. The second section specifically explores Arctic search and rescue, including its challenges and evaluated its future activity; with the third and final section investigating the available options for improving search and rescue in Canada. Essentially, Canada’s system was found to adequately meet general search and rescue requirements, however, it was found to be labouring to sustain itself and does not possess the capacity to withstand any substantial changes in need. Consequently, the system is finding it increasingly difficult to provide adequate and timely search and rescue services to the Arctic region; especially due to its remote, harsh and complex environment. Therefore as the Arctic’s rescue needs grow, the current system will increasingly be unable to meet them. As a result, without adjustments to Canada’s search and rescue system, it will lack the capacity to meet growing search and rescue demands in the Arctic.